2010
DOI: 10.1111/j.1445-2197.2010.05339.x
|View full text |Cite
|
Sign up to set email alerts
|

Wound infusion with local anaesthesia after laparotomy: a randomized controlled trial

Abstract: Local anaesthesia infusion at the fascial plane provides effective analgesia. This improves patient recovery through earlier return to bowel function and mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
3
26
1
Order By: Relevance
“…It is interesting to note that the studies by Forastiere et al [21] and Aguirre et al [17] which showed the largest effect sizes for the pain during mobilization and total opioid rescue variables also had two of the highest ropivacaine exposures over the first 24 h (580 and 636 mg, respectively). Contrasting these exposures with those from the studies of Ansaloni et al [23] and Wang et al [19] (260 and 192 mg, respectively) may suggest that the efficacy can be improved for some procedures by using higher ropivacaine exposures. This suggested dose-response relationship is further supported by the results of the study by Gottschalk et al [22], which demonstrated that an infusion rate of 18.75 mg/h significantly reduced pain at rest and during mobilization compared to a rate of 10 mg/h.…”
Section: Discussionmentioning
confidence: 39%
See 4 more Smart Citations
“…It is interesting to note that the studies by Forastiere et al [21] and Aguirre et al [17] which showed the largest effect sizes for the pain during mobilization and total opioid rescue variables also had two of the highest ropivacaine exposures over the first 24 h (580 and 636 mg, respectively). Contrasting these exposures with those from the studies of Ansaloni et al [23] and Wang et al [19] (260 and 192 mg, respectively) may suggest that the efficacy can be improved for some procedures by using higher ropivacaine exposures. This suggested dose-response relationship is further supported by the results of the study by Gottschalk et al [22], which demonstrated that an infusion rate of 18.75 mg/h significantly reduced pain at rest and during mobilization compared to a rate of 10 mg/h.…”
Section: Discussionmentioning
confidence: 39%
“…Another patient developed a transient ischaemic attack about 48 h after open hepatic surgery [28]. In another study [19], 1 control group patient had her morphine PCA terminated around 24 h after surgery due to excessive confusion and sedation. Across all included studies, there were no reports or signs of local anaesthetic systemic toxicity with all reported ropivacaine plasma concentrations below toxic levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations